Developing Annihilationist Strategies: Diversity, Equity, and Inclusion in The Racial Capitalist University - Shankar, Arjun (Radical Teacher, 2025)
In this article, I situate the story of my students in the university as a racial and gendered capitalist institution which requires and deploys diversity initiatives as part of its strategy to maintain its accumulative potential. Using several examples from my experiences with students on Georgetown’s campus, I show how such strategies produce an excess emotional stress for students of color, and women of color in particular, who are forced to participate in this form of labor on campus. I will then turn to the kinds of strategies – strategies which I term annihilationist – that we might deploy in our classrooms in order to begin to teach students the skills they need to protect themselves as they seek to overturn systems that produce so much of their unwellness. I evoke “annihilation” to center anti-caste and anti-colonial traditions that challenge the university’s rigid hierarchies and stratifications. "This is a correction to the original article. For information about the changes made, please see the erratum linked as a supplemental file on the article’s landing page. The information will also be available at https://radicalteacher.library.pitt.edu/ojs/radicalteacher/article/view/1394 in issue 132.”